Implikasi Penerapan Disiplin Petugas Lapangan Berbasis Elektronik dan Zonasi Wilayah Tugas pada Dinas Perhubungan Kota Bukittinggi - Frince Maradoni (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the effectiveness of implementing electronic attendance systems in improving employee discipline at the Transportation Agency. The research employed a qualitative descriptive method to provide an objective overview of the implementation process based on data collected from the field. Data were obtained through interviews, observations, and documentation involving relevant employees and institutional records. The results indicate that the implementation of electronic attendance and task area zoning has been effective in supporting employee discipline. The achievement of targets is demonstrated by improvements in attendance levels and the ease of preparing monthly attendance reports through the Bukittinggi Presence application, which records attendance data, personal reports, and monthly recapitulations. Furthermore, employees have shown good adaptability to the electronic attendance system, including fingerprint and mobile application usage, due to prior training, trials, and guidance from organizational administrators. The system also contributes to increased job satisfaction by motivating employees, improving time discipline, and supporting better public services. In terms of responsibility, electronic attendance encourages employees to complete assigned tasks more effectively due to the implementation of disciplinary sanctions and their impact on additional overtime incentives. Overall, electronic attendance provides a positive contribution to strengthening employee discipline, accountability, and service performance within the Transportation Agency.